The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.1155/2020/2589601
|View full text |Cite
|
Sign up to set email alerts
|

Public Health Implications of Solar UV Exposure during Extreme Cold and Hot Weather Episodes in 2018 in Chilton, South East England

Abstract: Consideration of the implications of solar UV exposure on public health during extreme temperature events is important due to their increasing frequency as a result of climate change. In this paper public health impacts of solar UV exposure, both positive and negative, during extreme hot and cold weather in England in 2018 were assessed by analysing environmental variations in UV and temperature. Consideration was given to people’s likely behaviour, the current alert system and public health advice. During a p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 56 publications
(86 reference statements)
2
4
0
Order By: Relevance
“…The results found the relationship between them is influential. The p-value is less than 0.001, which is consistent with the results [25] [3].…”
Section: Resultssupporting
confidence: 92%
See 2 more Smart Citations
“…The results found the relationship between them is influential. The p-value is less than 0.001, which is consistent with the results [25] [3].…”
Section: Resultssupporting
confidence: 92%
“…Therefore, workers should avoid working in the sun or using one of the personal UV protection methods, as shown in "Figure 4" Compared to UV exposure with the highest UV index every day "Table 6", The results found a relationship between them is influential. The pvalue is less than 0.001, consistent with the results [24] [3]. As well as, The UV exposure with the temperature for every day.…”
Section: Resultssupporting
confidence: 91%
See 1 more Smart Citation
“…Regarding the effects of phototoxicity, the contribution of different groups in the present study showed that exposed earthworms to UV-A caused the damage; this was the product of the work on earthworm Metaphire Posthuma (Chuang et al 2004;Misra et al 2005), who worked on three species of earthworms (Amynthas gracilis, Pontoscolex corethrurus, and Metaphire Posthuma) which, was explained the destructive impact of ultraviolet radiation on earthworms. In addition, some researchers addressed the health effects of solar UV exposure, which is complex and dependent on different sociodemographic variables, including skin colour (Rendell et al 2020). Earthworms (Lumbricus castaneus) were exposed to UV-C for 15 min each day showed little alterations (Abd El-Aziz and Ali 2021).…”
Section: Discussionmentioning
confidence: 99%
“…Public Health England (PHE) has a network of ground-based solar monitoring sites across the UK and overseas and additional spectral solar monitoring capabilities at Chilton, UK. These are used for health research and the development of advice regarding sun exposure (8)(9)(10)(11)(12).…”
Section: Introductionmentioning
confidence: 99%